(untitled) (Ameghiniana, 2019)
The species Dalmanella testudinaria (Dalman) was reported thirty years ago from the Hirnantian Don Braulio Formation of the Argentinean Precordillera, but its assignment was cast in doubt by a recent revision of the species. Through a detailed morphological analysis of a large collection of specimens, attribution of the Don Braulio Formation material to D. testudinaria is now confirmed. The overlying Rhuddanian sandstones of the La Chilca Formation yielded a dalmanellid which was previously referred to as Dalmanella aff. testudinaria. The minor differences existing between these specimens and the topotype material from Sweden is interpreted as intraspecific variation and consequently they are assigned to D. testudinaria. This implies that in the Precordillera basin this species survived the second pulse of the endOrdovician mass extinction. In the Don Braulio Formation largest shells occur in shallow-water subtidal carbonate lenses and siltstones, near the base of the posglacial transgression, reflecting deposition in well-oxygenated, nutrient-rich waters. Shell size decreases upsection reaching a minimum in the organic-rich mudstones bearing the graptolite Metabolograptus persculptus (Elles et Wood). Overall evidence suggests that low-richness and low-density of this community could be attributed to unfavorable physical environmental conditions associated with decreased food availability, and such limiting paleoecological factors are considered to be the primary cause of dwarfing. Small specimens of D. testudinaria reappear a few meters above the “extinction level” in the lower part of the La Chilca Formation of Rhuddanian age. Before becoming extinct, D. testudinaria coexisted in the Cuyania terrane with the first representatives of the Afro-South American Realm such as Anabaia Clarke and Heterorthella Harper, Boucot, And Walmsley. http://dx.doi.org/10.5710/AMGH.22.04.2019.3233